2020
DOI: 10.1186/s12957-020-01977-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positive surgical margin location and perineural invasion on biochemical recurrence in patients undergoing radical prostatectomy

Abstract: Objective To estimate the prognostic value of positive surgical margins (PSM) location and perineural invasion (PNI) for biochemical recurrence (BCR) in patients undergoing radical prostatectomy (RP). Methods All men with prostate cancer (PCa) who received RP in the second hospital of Tianjin Medical University from 2014 to 2018 were retrospectively identified. All patients met the following criteria: no neoadjuvant or adjuvant treatment, absence of lymph node invasion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…This conclusion indicated that lower LMR may have a worse prognosis in PCa patients (21). At the same time, Lian et al found that patients with apical PSMs had a higher risk of biochemical recurrence than patients with other PSMs in 2020 (22). These findings lead us to speculate that the impact of LMR on the prognosis of PCa patients may be caused by the incidence of apical PSMs after RP.…”
Section: Discussionmentioning
confidence: 87%
“…This conclusion indicated that lower LMR may have a worse prognosis in PCa patients (21). At the same time, Lian et al found that patients with apical PSMs had a higher risk of biochemical recurrence than patients with other PSMs in 2020 (22). These findings lead us to speculate that the impact of LMR on the prognosis of PCa patients may be caused by the incidence of apical PSMs after RP.…”
Section: Discussionmentioning
confidence: 87%
“…Perineural invasion (PNI) is regarded as a reasonable risk factor when incorporating all possible ways of tumour spread, and the prognostic impact of PNI has been demonstrated in many studies, including other cancers (25)(26)(27). The College of American Pathologists has highlighted the importance of PNI and recommended reporting PNI in patients with carcinoma of the colon and rectum since 2009(28).…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion (PNI) is regarded as a reasonable risk factor when incorporating all possible ways of tumour spread, and the prognostic impact of PNI has been demonstrated in many studies, including other cancers [ 24 26 ]. The College of American Pathologists has highlighted the importance of PNI and recommended reporting PNI in patients with carcinoma of the colon and rectum since 2009 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%